Metaphors we read by: People, process, and fan fiction - Juli J. Parrish (Transformative Works and Cultures, 2013)
New metaphors must be adopted for the writing of fan fiction. Henry Jenkins's metaphor of the textual poacher has achieved tacit acceptance and widespread circulation, suggesting that it has become relatively fixed as a description of fan creative practices among fans as well as in scholarship. Challenges to this model and metaphor are important but have not successfully displaced the prominence of the textual poacher. One promising alternative structure is that of Brownian motion, a scientific concept that both Michel de Certeau and Constance Penley have offered as a metaphor for creativity. Whereas textual poaching offers us a vision of fans as nomads, moving through a place and collecting materials, Brownian motion offers us a vision of fan fiction as world building, a process that remakes the place itself. Metaphors such as Brownian motion do not only offer us a different framework for understanding the creative processes that characterize fan fiction writing; they also remind us to focus on those creative processes themselves, as well as on the fans who engage in them.